TRADIÇÃO E PODER: A GRAMÁTICA DA LÍNGUA PORTUGUESA, DE JOÃO DE BARROS (1540) . - Patrícia Rafaela Otoni Ribeiro (Nepan editor, 2017)
This paper aims to reflect on the grammatical approach of João de Barros in the Gramática da língua portuguesa (Grammar of the Portuguese Language) (1540). Starting with an interpretative analysis and historically contextualization of Barros’s works such as A cartinha (The Abecedarium), Gramática da língua portuguesa and Diálogo em louvor da nossa linguagem (Dialogue in praise of our language), we highlight the influence of the Greek-Latin tradition is fundamental to the discourse and the grammatical structure of the author, also drawing upon the work of Bluescu (1978), Law (1987), Neves (1987), Auroux (1992), Baratin (1994) and Desbordes (1995). Furthermore, we underscore that the resort to Latin, in the historical moment of the Renaissance (XVI century), function as a comparison strategy aimed at propagating the hegemony of the Portuguese language and the Portuguese Empire.